1996
DOI: 10.1021/es9602004
|View full text |Cite
|
Sign up to set email alerts
|

Microanalysis of Museum Aerosols To Elucidate the Soiling of Paintings:  Case of the Correr Museum, Venice, Italy

Abstract: electron microscopy and scanning proton microprobe measurements on submicrometer indoor aerosol particles and giant indoor Ca-rich aerosol particles, respectively, are discussed as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…A number of studies have concluded that PM can lead to soiling due to large particles (diameter is larger than 2.5 µm) that are abrasive. Large particles may also cause surface scratching (Brimblecombe, 1990;Phenix and Burnstock, 1990;Nazaroff, 1993;De Bock et al, 1996). Particles within that size range are heavy enough to settle in a still air.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have concluded that PM can lead to soiling due to large particles (diameter is larger than 2.5 µm) that are abrasive. Large particles may also cause surface scratching (Brimblecombe, 1990;Phenix and Burnstock, 1990;Nazaroff, 1993;De Bock et al, 1996). Particles within that size range are heavy enough to settle in a still air.…”
Section: Introductionmentioning
confidence: 99%
“…Cluster analysis was performed for the standardized matrix (19 variables and 94 data sets) using Euclidian distances. 5,6 Results and Discussion 94 sample results for BTEXT are summarized in Table 1. These compounds represent the main volatile organic compounds (VOC) at ambient air and in the fuels.…”
Section: Discussionmentioning
confidence: 99%
“…Air quality in museums is critical to the preservation and conservation of rare antiquities [1][2][3][4][5][6][7], with damage from air pollution being firstly reported in the middle of the 19th century at the British Art Gallery [3]. Since the 1990s, the microclimate in museums and airborne pollutants originating from indoor activities and/or penetration from outdoors have been of increasing concern in Europe [5,[8][9][10][11] and the United States [4,12].…”
Section: Introductionmentioning
confidence: 99%